The Effect of Green Bean Consumption on Breast Milk Production in Breastfeeding Mothers in the Work Area of the Kedungmundu Health Center, Tembalang District, Semarang City - Ari Lestari, Nur Cahyani; Purwanti, Sri; Fathiyati (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2022)
This study aims to determine the effect. Green bean consumption on breast milk production in breastfeeding mothers in the working area of ​​the Kedungmundu Health Center, Tembalang District, Semarang City. The design in this study is a static group comparison/posttest only control group design, that is, a pre-experimental design. The data collection tool used is a questionnaire. The research sample was obtained by accidental sampling. The number of respondents in the study amounted to 34 respondents. The results showed that the milk production of breastfeeding mothers in the intervention group was mostly 12 respondents (70.6%) and 5 respondents (29.4%) had little breast milk production. Breast milk production of breastfeeding mothers in the control group was mostly a lot of 11 respondents (64.7%) and a little milk production of 6 respondents (35.3%). And it can be seen that p value = 0.005 (p value 0.05) so it can be concluded that there is an effect of green bean consumption on breast milk production in breastfeeding mothers in the working area of ​​Kedungmundu Public Health Center, Tembalang District, Semarang City.